Enlightening the Black Box of Humanities Research. Methodological Documentation as a Way to Transparency and Accountability of Digital Exhibitions - Sebastian Barzaghi; Alice Bordignon; Bianca Gualandi; Silvio Peroni (Umanistica Digitale)
This article discusses open and reproducible research on Cultural Heritage by presenting the digital twin of the exhibition “The Other Renaissance: Ulisse Aldrovandi and the Wonders of the World” as a case study. After an overview of “reproducibility”, “replicability” and “repeatability” in different research contexts it describes the acquisition and digitisation process, with a focus on the collection of metadata and paradata (e.g., acquisition techniques, individuals responsible, start and completion dates) and on the activities necessary to process, transform, and publish the digital cultural heritage objects and their metadata as FAIR and linked open data. We also describe how open technologies and software were employed throughout to maximise transparency, accountability and the workflow’s re-adoption for the creation of a virtual exhibition in different settings. Finally, we circle back to “reproducible expertise” and mention the obstacles that still exist to transparency and accountability in the scholarly ecosystem.